Even if they are not aware of it, general practitioners improve well-being in their adolescent patients. (2nd October 2017) - Tudrej, Benoit V.; Heintz, Anne-Laure; Rehman, Michaela B.; Marcelli, Daniel; Ingrand, Pierre; Binder, Philippe
Abstract: Background: Most adolescents consult their general practitioner (GP) for common reasons, somatic or administrative but many of them have hidden feelings of distress. Objectives: To assess the immediate impact of 'ordinary' consultations on feelings of distress among adolescents and to compare adolescents experiencing difficulties (D) to those with no difficulties (N). To analyse how accurately GPs assess the impact of their consultation on adolescents' feelings. Methods: GPs were randomly selected from two non-contiguous French administrative areas between April and June 2006. Fifty-three GPs gave two questionnaires to the first 10 to 15 adolescents aged 12 to 20 seen in consultation. One questionnaire was issued before the consultation and the other one afterwards. Adolescents had to position themselves about different aspects of well-being and say where they would seek help if they had problems. A GP questionnaire assessed how well they estimated their impact on the adolescent's feeling of well-being. Results: Six hundred and sixty-five adolescents were assessed. They reported feeling better about their health, being able to talk, having someone to talk to or to confide in and on feeling understood. The D group ( n = 147) felt significantly better compared to the N group ( n = 518). GPs tended to underestimate this improvement, especially regarding adolescents in the D group feeling better about their health. Conclusions: Consulting a GP generates increased well-being among adolescents, especially for those experiencing difficulties. GPs tend to underestimate the positive impact they may have. Further studies are needed to explore if this benefit is permanent over time.